2003
DOI: 10.1080/0954026021000046047
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of psychiatric morbidity among adults living in institutions

Abstract: This paper presents prevalence data from the 1994 OPCS survey of psychiatric morbidity among adults permanently resident in institutions catering for people with mental health problems in Great Britain. It describes briefly the survey methods used, and how diagnoses of psychiatric morbidity were derived. Its main aim is to show the prevalence of psychiatric morbidity in different types of institutional settings. Residents were eligible for the survey if they were aged 16 to 64 at the date of sampling and were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
136
3
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(149 citation statements)
references
References 0 publications
7
136
3
3
Order By: Relevance
“…Further information about drug use, in the past year and in the past month, was collected for cannabis, amphetamines, crack, ecstasy, tranquillizers, opiates and volatile substances, such as glue. These questions, originally used in the 1993 survey (Meltzer et al 1995), were amended slightly to bring them in line with those used in the British Crime Survey (Ramsay & Partridge, 1999). Included in the questions about drug use in the past year and month were five questions, taken from the Epidemiologic Catchment Area study (Robins & Regier, 1991) and used in other previous Office for National Statistics psychiatric morbidity surveys, to measure drug dependence, indicated by a positive response to any one of them.…”
Section: Assessment Of Mental Disordermentioning
confidence: 99%
“…Further information about drug use, in the past year and in the past month, was collected for cannabis, amphetamines, crack, ecstasy, tranquillizers, opiates and volatile substances, such as glue. These questions, originally used in the 1993 survey (Meltzer et al 1995), were amended slightly to bring them in line with those used in the British Crime Survey (Ramsay & Partridge, 1999). Included in the questions about drug use in the past year and month were five questions, taken from the Epidemiologic Catchment Area study (Robins & Regier, 1991) and used in other previous Office for National Statistics psychiatric morbidity surveys, to measure drug dependence, indicated by a positive response to any one of them.…”
Section: Assessment Of Mental Disordermentioning
confidence: 99%
“…The schedule can be used both to provide a total symptom score and to generate a diagnosis according to the International Classification of Diseases (ICD-10) 27 using the algorithm used in the Office of Population Censuses and Surveys (OPCS) national surveys of psychiatric morbidity in Great Britain. 28 The computerised version of the CIS-R (PRQSY3), which is self-complete, was used in the present study.…”
Section: Psychiatric Symptomsmentioning
confidence: 99%
“…A study that has examined parental wellbeing during offspring's adolescence suggests that women with little investment in paid work are most at risk (Silverberg, 1996). While most studies have shown that women with children at home are more likely to be depressed than others (Meltzer, Gill, Petticrew, & Hinds, 1995;McLanahan & Adams, 1989), the quality of the specific role experience is generally regarded as more important to a woman's mental health (Bromberger, 1998). The higher distress levels for women in our study who were older at the birth of their children may reflect the restrictions this imposed on their lifestyle relative to that of their peers who had their children at younger ages.…”
Section: Adult Health and Social Circumstancesmentioning
confidence: 99%